Temperature effect on mechanical and physical proprieties of Na or K alkaline silicate activated metakaolin-based geopolymers - Nmiri, Ahmed; Yazoghli-Marzouk, Oumaya; Duc, Myriam; Hamdi, Noureddine; Srasra, Ezzeddine (Italian journal of engineering geology and environment, 2016)
<span data-sheets-value="{"1":2,"2":"In this work geopolymeric materials were synthesized in order to reach the best thermal characteristics allowing the use of them as flame retardant natural stone. The mechanical strength (notably after high temperature exposure) as well as the microstructure were investigated on hardened specimens of geopolymer manufactured at ambient temperature with metakaolin and a mixture of alkali hydroxide solution (MOH) and alkali silicate solution (M2SiO3) with M = K or Na. Geopolymers were subjected to thermogravimetric analysis, scanning electron microscopy and mercury intrusion porosimetry tests and linear shrinkage, loss on ignition and compressive strength measurements. Results showed that Na-Mk geopolymer exhibits higher compressive strength at ambient temperature after the curing, du to a minor value of porosity compared to the value for the K-Mk geopolymer. Na-Mk geopolymer gave a geopolymer with a high degree of condensation compared to K-Mk geopolymer because the dissolution of aluminosilicate precursor is still greater in presence of Na+ cations than in presence of K+ cations. The strength of the Na or K-based geopolymer decreased after exposure to elevated temperatures (until 600°C). The conclusion of the study is that Na-Mk geopolymer is the most appropriate for using in the production of thermal resistant geopolymer cement than K-Mk based geopolymer."}" data-sheets-userformat="{"2":15233,"3":{"1":0},"10":1,"11":3,"12":0,"14":{"1":2,"2":0},"15":"Arial","16":8}">In this work geopolymeric materials were synthesized in order to reach the best thermal characteristics allowing the use of them as flame retardant natural stone. The mechanical strength (notably after high temperature exposure) as well as the microstructure were investigated on hardened specimens of geopolymer manufactured at ambient temperature with metakaolin and a mixture of alkali hydroxide solution (MOH) and alkali silicate solution (M2SiO3) with M = K or Na. Geopolymers were subjected to thermogravimetric analysis, scanning electron microscopy and mercury intrusion porosimetry tests and linear shrinkage, loss on ignition and compressive strength measurements. Results showed that Na-Mk geopolymer exhibits higher compressive strength at ambient temperature after the curing, du to a minor value of porosity compared to the value for the K-Mk geopolymer. Na-Mk geopolymer gave a geopolymer with a high degree of condensation compared to K-Mk geopolymer because the dissolution of aluminosilicate precursor is still greater in presence of Na+ cations than in presence of K+ cations. The strength of the Na or K-based geopolymer decreased after exposure to elevated temperatures (until 600°C). The conclusion of the study is that Na-Mk geopolymer is the most appropriate for using in the production of thermal resistant geopolymer cement than K-Mk based geopolymer.